Powdery Mildews in the Libyan Jamahiriya: I. Identity of Certain Powdery Mildew Fungi - KHAN, M. WAJID; MUSSA, AHMED E. A. (The Libyan Journal of Agriculture, 2023)
An attempt has been made to enlist and identify the powdery mildews infecting cultivated and wild plants in Libyan Jamahiriya. This paper is the first in the series and includes Erysiphe heraclei, Erysiphe sordida, Erysiphe ciohoracearum, and Erysiphe graminis. All the four species exhibited perithecial production in nature on their respective hosts. E. cichoracearum was found on Amerboa lippii and this host is an addition to the host index of the species. The occurrence of E.graminis on Bromus diandrus is also a new record.